Pengaruh Kesadaran Perpajakan, Pengetahuan Dan Pemahaman Tentang Perpajakan, Persepsi Yang Baik Atas Efektifitas Perpajakan Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Bekasi Utara) - Fitri Endang Febriyani; Bambang Irawan (Jurnal Ilmu Administrasi Publik, 2023)
Tax Awareness is the obedience of taxpayers to carrying out their Tax Obligations following appliance regulations. Understanding of Taxes and the Level of Awareness, which increases public knowledge and understanding of taxation so that it has a positive impact on the Awareness of Taxpayers to pay their obligations. This study aims to determine how the influence of awareness of paying Taxes, Knowledge, and Understanding of Taxation, and a Good Perception of the Effectiveness of Taxation and Tax Authorities on individual Taxpayer Compliance. The population and sample of this study are individual Taxpayers who are registered at the North Bekasi Primary Tax Service Office. The sampling technique was carried out using questionnaire data from 110 respondents. Based on the results of data processing through the SPSS Staticts 25 software which has been analyzed, there is a positive influence between Tax Awareness (X1), Tax Knowledge and Understanding (X2), Good Perception of Tax Effectiveness (X3), and Fiscal Services (X4) on Personal Taxpayer Campliance (Y).